Literature Review Kesehatan dan Keselamatan Kerja Pelayanan Radioterapi pada Penggunaan Pesawat Linac - Ira Sandi Tunny; Rini Hatma Rusli; Maritje S. J. Malisngorar; Iksan Soumena; Miranda Waas (Pusat Riset dan Inovasi Nasional, 2022)
Occupational Health and Safety are conditions in work that are healthy and safe, both for the job, the company and for the community and environment around the factory or workplace. One of the K3 Standards according to the Ministry of Health as intended in paragraph (1) is aimed at preventing and reducing occupational diseases and other illnesses, as well as work accidents among employees, and creating safe, comfortable and efficient offices to encourage work productivity.The research method used in this research is library research which uses literature as the main object. This research carried out descriptive analysis, namely trying to describe the Occupational Health and Safety of Radiotherapy services when using LINAC aircraft. To find out Occupational Health and Safety in Radiotherapy services, researchers reviewed several literature including books, articles and journals related to Occupational Health and Safety in Radiotherapy services in several hospitals in Indonesia. The research results show that creating occupational health and safety in radiodiagnostic and radiotherapy services requires component compatibility. Good equipment, examination room design that complies with the rules, appropriate procedures, security systems, health monitoring of officers and policies from the highest responsible persons.